Invisible cervical cancers on MRI: Can the type of histology (SCC versus non-SCC) influence surgical planning? - Jeon, Jungeun; Park, Byung Kwan; Lee, Jeong-Won; Choi, Chel Hun; Lee, Yoo-Young; Kim, Tae-Joong; Kim, Byoungi-Gie (Frontiers in Oncology, 2022)
Background Invisible cervical cancers on MRI can indicate less invasive surgery. Cervical cancers consist of squamous cell carcinoma (SCC) and non-SCC, each with different long-term outcomes. It is still unclear if surgical planning should be changed according to the histologic type of cervical cancer when it is not visible on MRI. Purpose The purpose of the study was to determine if surgical planning for cervical cancer that is not visible on MRI is influenced by the histologic type. Materials and methods Between January 2007 and December 2016, 155 women had Federation of Gynecology and Obstetrics (FIGO) stage 1B1 cervical cancer that was not visible on preoperative MRI. They underwent radical hysterectomies and pelvic lymph node dissections. Among them, 88 and 67 were histologically diagnosed with SCC and non-SCC, respectively. The size of the residual tumor, depth of stromal invasion, parametrial invasion, vaginal invasion, lymphovascular invasion, and lymph node metastasis were compared between these patients using the t-test, Mann–Whitney U test, Chi-squared test, or Fisher’s exact test. The recurrence-free and overall 10-year survival rates were compared between the groups by Kaplan–Meier analysis. Results The mean sizes of residual tumors were 8.4 ± 10.4 mm in the SCC group and 12.5 ± 11.9 mm in the non-SCC group (p = 0.024). The mean depth of stromal invasion in the SCC group was 12.4 ± 21.2% (0%–100%), whereas that in the non-SCC group was 22.4 ± 24.4 (0%–93%) (p = 0.016). However, there was no difference in parametrial or vaginal invasion, lymphovascular invasion, or lymph node metastasis (p = 0.504–1.000). The recurrence-free and overall 10-year survival rates were 98.9% (87/88) and 95.5% (64/67) (p = 0.246), and 96.6% (85/88) and 95.5% (64/67) (p = 0.872), respectively. Conclusions The non-SCC group tends to have larger residual tumors and a greater depth of stromal invasion than the SCC group, even though neither is visible on MRI. Therefore, meticulous care is necessary for performing parametrectomy in patients with non-SCC cervical cancer.